P023: The BC Emergency Medicine Network: Evaluation approach and early findings. (May 2019) - Marsden, J.; Drebit, S.; Lindstrom, R.; MacKinnon, C.; Archibald, C.; Abu-Laban, R.; Eggers, K.; Ho, K.; Khazei, A.; Lund, A.; Martin, E.; Christenson, J.
Abstract : Introduction : September 2017 saw the launch of the British Columbia (BC) Emergency Medicine Network (EM Network), an innovative clinical network established to improve emergency care across the province. The intent of the EM Network is to support the delivery of evidence-informed, patient-centered care in all 108 Emergency Departments and Diagnostic & Treatment Centres in BC. After one year, the Network undertook a formative evaluation to guide its growth. Our objective is to describe the evaluation approach and early findings.Methods : The EM Network was evaluated on three levels: member demographics, online engagement and member perceptions of value and progress. For member demographics and online engagement, data were captured from member registration information on the Network's website, Google Analytics and Twitter Analytics. Membership feedback was sought through an online survey using a social network analysis tool, PARTNER (Program to Analyze, Record, and Track Networks to Enhance Relationships), and semi-structured individual interviews. This framework was developed based on literature recommendations in collaboration with Network members, including patient representatives.Results : There are currently 622 EM Network members from an eligible denominator of approximately 1400 physicians (44%). Seventy-three percent of the Emergency Departments and Diagnostic and Treatment Centres in BC currently have Network members, and since launch, the EM Network website has been accessed by 11, 154 unique IP addresses. Online discussion forum use is low but growing, and Twitter following is high. There are currently 550 Twitter followers and an average of 27 'mentions' of the Network by Twitter users per month. Member feedback through the survey and individual interviews indicates that the Network is respected and credible, but many remain unaware of its purpose and offerings.Conclusion : Our findings underscore that early evaluation is useful to identify development needs, and for the Network this includes increasing awareness and online dialogue. However, our results must be interpreted cautiously in such a young Network, and thus, we intend to re-evaluate regularly. Specific action recommendations from this baseline evaluation include: increasing face-to-face visits of targeted communities; maintaining or accelerating communication strategies to increase engagement; and providing new techniques that encourage member contributions in order to grow and improve content.